2018
DOI: 10.1016/j.iccn.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ views of smart glasses in intensive care: A qualitative study

Abstract: Smart glasses are suggested as a complement to existing monitoring and routines and cannot replace human presence in intensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 21 publications
1
24
0
4
Order By: Relevance
“…A similar previous study explored health care professionals' views of smart glasses in intensive care setting. 18 In line with our results, participants in that study also believed that smart glasses can enhance communication within the team, especially when team members are working in different locations. Both studies show, moreover, that participants believe it is important, especially in emergency situations, to avoid the risk of distraction and confusion by making smart glasses display configuration similar (in terms of views, layout, and colors) to what they are familiar with from existing monitoring equipment.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A similar previous study explored health care professionals' views of smart glasses in intensive care setting. 18 In line with our results, participants in that study also believed that smart glasses can enhance communication within the team, especially when team members are working in different locations. Both studies show, moreover, that participants believe it is important, especially in emergency situations, to avoid the risk of distraction and confusion by making smart glasses display configuration similar (in terms of views, layout, and colors) to what they are familiar with from existing monitoring equipment.…”
Section: Discussionsupporting
confidence: 86%
“…The study conducted in an intensive care setting 18 and our study show some differences among health care professionals. In intensive care, they focused more on the importance of interpersonal relationships between health care professionals and patients, and on how smart glasses might possibly affect these relationships.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Aligning more closely with the interests of our research, the third ICU/smart-glasses study (Romare, Hass, & Skär, 2018) addressed (in greater part) the challenges identified in our study. For example, in this study, researchers gathered findings from interviewing ICU physicians on the use of smart glasses to support clinical work.…”
Section: Related Workmentioning
confidence: 88%
“…SG require a tailored software (application) for each context and purpose [15,16]. HCPs' requests regarding both quality of use and desired VSs to make SG a tool for clinical monitoring of VSs and a part of surveillance has recently been described [17,18]. The innovation project SUCCCE used i.a.…”
Section: Smart Glasses For Anesthesia Carementioning
confidence: 99%